THE INFLUENCE OF PERCEIVED VALUE ON PASSENGER LOYALTY WITH PASSENGER SATISFACTION AS A MEDIATING VARIABLE (CASE STUDY: LION AIR PASSENGERS IN PADANG CITY) - Bambang Sugino; Sefnedi Sefnedi; Reni Yuliviona (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Customer loyalty has received considerable attention from both academics and practitioners. However, the various factors that can explain customer loyalty have not yet been clearly defined. This study examines the role of passenger satisfaction as a mediator between perceived value and loyalty. The population in this study is all passengers using Lion Air in 2024 at Minangkabau International Airport, West Sumatra Province, Indonesia. The total research sample was 150 people. Respondents were obtained by using a sampling technique or purposive sampling. The data analysis used was Structural Equation Model (SEM) using Smart-PLS version 3.2.9. The results showed that perceived value had a positive effect on both passenger satisfaction and passenger loyalty. Passenger satisfaction also has a positive effect on passenger loyalty. Furthermore, passenger satisfaction mediates the relationship between perceived value and passenger loyalty. Keywords : Perceived value, Passenger satisfaction, Customer loyalty